Acute disseminated encephalomyelitis following Campylobacter jejuni gastroenteritis: Case report and review of the literature. Issue 1 (February 2017) - Marziali, Simone; Picchi, Eliseo; Di Giuliano, Francesca; Altobelli, Simone; Mataluni, Giorgia; Marfia, Girolama; Garaci, Francesco; Floris, Roberto
We describe a case of a 25-year-old male with a diagnosis of acute disseminated encephalomyelitis (ADEM) following infection with Campylobacter jejuni, which is implicated in various human pathologies regarding the central nervous system (CNS) with acute course like Guillain-Barré syndrome (GBS), Miller-Fisher syndrome (MFS), Bickerstaff's brainstem encephalitis (BEE), acute transverse myelitis (ATM) as well as ADEM. These conditions are caused by cross-reactivity between Campylobacter's epitopes and cells of the CNS that causes an immunomediated inflammatory demyelination of the CNS. In the acute phase, magnetic resonance (MR) can detect pathologic signal intensity at the CNS with areas of pathologic contrast enhancement at cortical and spinal white matter that normalize over time or can be stable. These findings can be associated with edema in parts of the CNS. The lesions typically appear at different times during the disease course and also can have a different evolution. Our purpose therefore was to describe the clinical course and MR findings of this case and perform a critical review of the literature.